Pengaruh Asfiksia terhadap Ukuran Kepala Anak Usia 6 Bulan - 2 Tahun di Rumah Sakit Umum Provinsi Nusa Tenggara Barat - Melati Inayati Albayani; Djauhar Ismail; Mei Neni Sitaresmi (Fakultas Kedokteran, Kesehatan Masyarakat dan Keperawatan UGM, 2018)
Background: In developing countries is estimated at about 120 million babies born asphyxiated at birth. Among these who can survive 20% to 30% had mental disorder, cerebral palsy or developmental abnormality due to the small size of head circumference (microcephaly).Objective: To determine the effect of asphyxia on the head circumference size of children age 6 months - 2 years.Method: A matched case-control study design was conducted from May – June 2014. The population of the study was all children age 6 months - 2 years who visited the Growth development clinic of General Hospital of West Nusa Tenggara Province. The cases were children who have microcephaly and the controls were children with normocephaly. From sample size which was calculated by hypothesis testing two populations proportions are obtained a sample of 72 respondents with 36 cases and 36 controls. Bivariate analysis used chi-square (χ2) McNemar and multivariable analysis with logistic regression (conditional logistic regression) with a significance level of p <0.05 and 95% confidence intervals.Result and Discussion: Microcephaly was present in 83 % of the children with asphyxia, compared with 36 % of the controls. The children with asphyxia tent to have microcephaly compared to children without asphyxia (OR = 5,00; 95% CI: 1,36-18,32). Results of multivariable analysis showed that there was a statistically significant effect between asphyxia with head circumference size by controlling the low birth weight variable (OR = 5,00; 95% CI: 1,36-18,32).Conclusion: History of asphyxia increases the risk of microcephaly compared with non-asphyxia in children aged 6 months - 2 years.Keywords: asphyxia, head circumference, children aged 6 months-2 years